2021
DOI: 10.1038/s41550-020-01284-x
|View full text |Cite
|
Sign up to set email alerts
|

The large obliquity of Saturn explained by the fast migration of Titan

Abstract: The obliquity of a planet is the tilt between its equator and its orbital plane. Giant planets are expected to form with near-zero obliquities [1,2]. After its formation, some dynamical mechanism must therefore have tilted Saturn up to its current obliquity of 26.7 • . This event is traditionally thought to have happened more than 4 Gyrs ago during the late planetary migration [3,4,5] because of the crossing of a resonance between the spin-axis precession of Saturn and the nodal orbital precession mode of Nept… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 28 publications
(79 reference statements)
2
54
0
Order By: Relevance
“…In our case, Titan largely dominates the satellite's contribution, and it is almost in the close-in regime (L 6 ε). We can therefore use the same trick as Saillenfest et al (2021) and replace Eq. (5) bỹ…”
Section: Equations Of Motionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our case, Titan largely dominates the satellite's contribution, and it is almost in the close-in regime (L 6 ε). We can therefore use the same trick as Saillenfest et al (2021) and replace Eq. (5) bỹ…”
Section: Equations Of Motionmentioning
confidence: 99%
“…For years, the scenarios that were most successful in reproducing Saturn's current obliquity through this resonance invoked the late planetary migration Boué et al 2009;Vokrouhlický & Nesvorný 2015;Brasser & Lee 2015). However, Saillenfest et al (2021) have recently shown that this picture is incompatible with the fast tidal migration of Titan detected by Lainey et al (2020) in two independent sets of observations -assuming that this migration is not specific to the present epoch but went on over a substantial interval of time. Indeed, satellites affect the spin-axis precession of their host planets (see e.g.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations